An Elegant Solution to a Ruptured Right Aberrant Subclavian Artery after Oesophageal Stent Removal. (12th April 2021) - Thompson, Daniel; Cerutti, Sophie; Peerbux, Muhammad; Ikponmwosa, Anna; Bookun, Hansraj; Lahham, Yahya
Abstract : Arterioenteric or arteriotracheal fistula is a known complication of an aberrant right subclavian artery (ARSA) and is often associated with prolonged nasogastric or endotracheal intubation or oesophageal stenting. Fistula formation from the ARSA can present unexpectedly with rapid exsanguination with massive haemoptysis or haematemesis, and unless promptly recognised and treated is rapidly fatal. We present a novel endovascular method for treating a fistula between the oesophagus, trachea and an ARSA in an unstable patient following oesophageal stent removal, utilising a covered iliac limb stent, eliminating the need for an open surgical approach.